KONVENSI BAHASA DAN HARMONISASI SOSIAL: Telaah Linguistik dalam Percakapan Campur Bahasa Arab - Jawa dan Kontribusinya Terhadap Harmonisasi Sosial di Masyarakat â€œKampung Arabâ€ Klego - Pekalongan - Muhandis Azzuhri (Jurnal Penelitian, 2011)
This research is aimed to analyze linguistic amalgamation among Arabian and Javanese inhabitants of Klego Pekalongan. The results showed the formed of linguistics convention in communication, based on linguistics rule (derivation and lexicon) and this convention contributed toward social harmonization among both of them. The indication of linguistics convention revealed from the compatibility and incompatibility of linguistics rule (derivation and lexicon). The convention took a place and diffused peacefully among Arabic and Javanese (linguistic acculturation), so itâ€™s pretty hard to distinguish between Arabic Descent and Javanese Descent in Klego in oral communication. The research used translation code-mixing code theory to analyze the problems. In order to acquire data, it emphasized in the primary data rather than the secondary one (as complement). The primary data were formed from linguistics data of communication in listening-speaking and recording. The data were presented using functional- descriptive analysis.